Prevalence of loneliness, anxiety, and depression among older people living in long-term care: A review - Syed Elias, Sharifah Munirah (IIUM Press, 2018)
Objective: The aim of this paper was to review prevalence rates of loneliness, anxiety, and depression among older people living in long-term care settings such as residential aged care facilities, nursing homes and assisted living facilities. Method: A systematic search of the literature was conducted using several electronic databases including Medline, CINAHL, PsycINFO, and the Cochrane library. Results: In total, 18 articles met the inclusion criteria for this review. The results indicated that the prevalence rates of loneliness (56% to 95.5%), anxiety (3.6% to 38%), and depression (11% to 85.5%) in older people living in long-term care settings are generally high. Conclusion: Further research on effective methods of reducing these symptoms is recommended.